Secondary ion mass spectrometry and low-energy ion scattering of II-V semiconductor hetero-structures - Laserna-Vázquez, José Javier; Padilla, D.; Vadillo-Pérez, José Miguel (Sociedad Española de Química Analítica, 2013)
Comunicación oral presentada durante la XVIII reunión de la Sociedad Española de Química Analítica y VI reunión Nacional de la Sociedad Española de Espectrometría de MAsas
Keywords: Química analítica; Células solares; Heteroestructuras; SIMS; Heterostructures; Solar cells